Use of endo-bronchial end-tidal CO2 test for location of the pleural air leakage in patients with intractable pneumothorax. (22nd February 2018) - Zeng, Yi-Ming; Chen, Yun-Feng; Lin, Hui-Huang; Zhang, Xiao-Bin
Background: Location of the affected bronchus of pleural air leaks is the most important step of trans-bronchoscopic bronchial occlusion for the treatment of intractable pneumothorax. The balloon occlusion test is the most commonly used technique, but has failed in some cases. The aim of the present study was: (1) to determine if endo-bronchial end-tidal CO2 (EtCO2 ) measurement can identify the affected bronchus that is the source of a persistent pleural air leak; and (2) to establish a methodology for endo-bronchial EtCO2 testing in locating affected bronchus in intractable pneumothorax. Methods: A total of 28 patients with intractable pneumothorax underwent bronchoscopy with (1) the balloon occlusion test for the identification of the affected bronchus; and (2) endo-bronchial EtCO2 measurement (EtCO2 test) at the orifices of the bronchus of the affected lung. The effectiveness of these two methods of affected bronchus identification were compared. The threshold EtCO2 (T-EtCO2 ) was determined. Results: The positive rates of locating the affected bronchus by the endo-bronchial EtCO2 test, balloon occlusion test, and combination of the two techniques were 60.7% (17/28), 64.3% (18/28) and 96.4% (27/28), respectively. The average differences in EtCO2 between the affected bronchus and the main carina, main bronchus, and non-affected bronchus were (in mmHg) 4.41 ± 1.99 (95% confidence interval: 3.5, 5.3), 4.73 ± 2.10 (3.80, 5.66 ) and 5.57 ± 2.53 (4.45, 6.69), respectively. Conclusions: (1) The endo-bronchial EtCO2 test is complementary to the balloon occlusion test of the leading bronchus. (2) A threshold (T-EtCO2 ) value of >5 mmHg is optimal for this technique.